047 Flying blind: investigating the validity of the revised child anxiety and depression scale in the medically unexplained symptoms population. (December 2018) - Jassal, K; Taylor, C; Hadji-Michael, M; Heyman, I; Stark, D
Abstract : Background: Medically Unexplained Symptoms (MUS) refer to physical symptoms for which there is no known physical cause. In paediatric MUS populations, high-rates of both neurodevelopmental and mental-health difficulties (50%–66%, Rawat, 2015) have been identified. However, such studies also suggest that individuals with MUS under-report emotional difficulties. Whilst many explanations for this phenomenon are possible, one long-standing hypothesis relates to inherent difficulties in individual's ability to both identify and describe their emotional state (Erkic, 2017). This is a pertinent clinical issue as there are high rates of mental difficulties in this population; however routine clinical instruments have not yet been validated in this group of children. This study investigated the validity of The Revised Child Anxiety and Depression Scale (RCADS; Chorpita et al., 2005); a measure routinely used to screen for anxiety disorders in children, with parallel parent and child versions. Methods: The current study aimed to investigate the validity of the RCADS in an MUS population. This study included children with MUS who attended a specialist multidisciplinary clinic for a comprehensive mental-health assessment between February 2011 and January 2018. All children who attended the clinic with MUS who completed either a parent-rated and/or self-rated RCADS were included in the study. Results: Thirty-eight children were included in the analysis. Sensitivity and specificity of both parent and child reports on the RCADS were analysed and compared to the sensitivity and specificity of previously validated populations (Becker et al., 2017). This study found that the RCADS correctly captured ˜80% of cases with no clinical symptoms of anxiety but only correctly identified those children with a clinical diagnosis of anxiety around 50% of the time. Conclusion: The RCADS does not consistently identify anxiety disorders within the paediatric MUS population. Clinical implications and considerations for future research are discussed.